2014
DOI: 10.1371/journal.pone.0099229
|View full text |Cite
|
Sign up to set email alerts
|

Response of Last Instar Helicoverpa armígera Larvae to Bt Toxin Ingestion: Changes in the Development and in the CYP6AE14, CYP6B2 and CYP9A12 Gene Expression

Abstract: Bt crops are able to produce Cry proteins, which were originally present in Bacillus thuringiensis bacteria. Although Bt maize is very efficient against corn borers, Spanish crops are also attacked by the earworm H. armigera, which is less susceptible to Bt maize. Many mechanisms could be involved in this low susceptibility to the toxin, including the insect's metabolic resistance to toxins due to cytochrome P450 monooxygenases. This paper examines the response of last instar H. armigera larvae to feeding on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…A set of miRNAs were found to target several families of important genes that are often involved in insecticide resistance, such as cytochrome P45025262728, esterase29, GSTs30, ABC transporter family protein3132, cuticle protein33, glutamate-gated chloride channel3435 and superoxide dismutase (SOD)36. The target genes of some selected miRNAs are listed in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…A set of miRNAs were found to target several families of important genes that are often involved in insecticide resistance, such as cytochrome P45025262728, esterase29, GSTs30, ABC transporter family protein3132, cuticle protein33, glutamate-gated chloride channel3435 and superoxide dismutase (SOD)36. The target genes of some selected miRNAs are listed in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…The findings that sublethal concentrations of insecticides including chlorantraniliprole may disturb insect hormone balance are somewhat intriguing. While chlorantraniliprole targets ryanodine receptor, an intracellular calcium (Ca 2+ ) release channel, and calcium (Ca 2+ ) is a key second messenger that plays important physiological roles in various cells, it seems unlikely that the specific mode of action of chlorantraniliprole contributes to its effect on hormone biosynthesis since similar effects were also observed in other insecticides with different modes of action . Alternatively, the potential interrelation of xenobiotic responses and hormonal regulation of insect development might provide insights into the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that insecticides are likely to interact with secondary sites of action, which may not lead to the death of the insect pests but may produce sublethal effects . Recently, several lines of evidence have indicated that sublethal concentrations of insecticides may affect fitness‐related traits by disturbing insect hormone balance; while the underlying mechanisms remain poorly studied, it has been suggested that sublethal concentrations of insecticides may compromise homeostasis of insect pests and change the gene expression in components of hormone biosynthesis pathways …”
Section: Introductionmentioning
confidence: 99%
“…Muñoz et al () showed that Bt‐susceptible H. armigera larvae which were fed sub‐lethal amounts of Bt toxin reduced food ingestion, growth and weight, which did not allow the majority of them to achieve a critical weight to pupate. Food intake increased when larvae were moved from Bt diet to non‐Bt diet.…”
Section: Discussionmentioning
confidence: 99%